Preliminary results for an economic exchange game designed to measure of an aspect of antisocial behavior. (October 2016) - Clark, C. Brendan; Weaver, Newal; Li, Ye; Sharp, Carla; Bowerman, Shannon E.; Cropsey, Karen L.
Abstract: This study provides preliminary evidence for an economic exchange game (Thieves' Game), to measure the effects of a lack of guilt or remorselessness on behavior. The study examined the relationship between performance in the Thieves' Game, antisocial personality traits, and self-report of guilt. The sample was composed of 169 community volunteers. Points stolen in the Thieves' Game, male gender, Machiavellianism, Neuroticism, lower Agreeableness, lower Conscientiousness, and lower concern over harming others, were all found to correlate with antisocial traits. When these significant associations were entered into a hierarchical linear regression, with gender, Machiavellianism, Neuroticism, Agreeableness, Conscientiousness, and concern over harming others entered in the first step and Thieves' Game performance entered in the second step, the Thieves' Game was a significant predicator and was responsible for a statistically significant R-squared change . In a second set of analyses designed to assess the relationship between guilt and stealing behavior in the Thieves' Game, a linear regression using self-report of guilt to predict stealing behavior while controlling for the effects of demographics and personality traits demonstrated that self report of experienced guilt was the only significant predictor of stealing behavior. Highlights: This study provides preliminary support for a new economic exchange game (Thieves' Game). The study examined the relationship between stealing behavior and antisocial personality traits. Stealing behavior in the Thieves' Game was a significant predicator of antisocial personality traits. Self-report of guilt was a significant predictor of greater stealing behavior in the Thieves' Game.